On the solutions and conserved vectors for the two-dimensional second extended Calogero-Bogoyavlenskii-Schiff equation - Chaudry Masood Khalique; Anila Mehmood (Results in Physics, 2021)
This paper studies the second extended Calogero-Bogoyavlenskii-Schiff (eCBS) equation in (2+1)–dimensions, which was proposed in the literature a short time ago. Firstly, Lie symmetries of the equation are derived and thereafter we use them to perform symmetry reductions. Using its translation symmetries, the eCBS equation is reduced to a fourth-order ordinary differential equation, which is then solved with the aid of three techniques to construct closed-form solutions. In addition, we portray the solutions with the appropriate graphical representations. Furthermore, conserved vectors of eCBS equation are computed by invoking multiplier procedure as well as Noether’s theorem.